Clinical and endoscopic analysis of gastrointestinal bleeding during COVID-19 full-blown pandemic: a retrospective cohort study - Jing-Wei Liu; Yue Sui; Jun-Hui Lu; Jin-Nan Ren; Jing-Wen Gong; Cui-Ping Xu; Yi Zhao; Xing Chen (Annals of Medicine, 2025)
Background Although endoscopy is a commonly used technique in patients with gastrointestinal bleeding (GIB), there is currently insufficient evidence to inform clinicians on how to manage patients with gastrointestinal bleeding during COVID-19 full-blown pandemic. Herein, we analyzed the clinical and endoscopic characteristics of GIB in patients hospitalized during COVID-19 full-blown pandemic.Methods Patients with GIB during the initial stage of COVID-19 pandemic and COVID-19 full-blown pandemic were enrolled and defined as Group 1 and Group 2, respectively. Comeparing the differences in the 30 days mortality, the need for intensive care unit (ICU) level of care, laboratory examination, blood transfusion and anticoagulant therapy, use of non-steroidal anti-inflammatory drugs (NSAIDs), frequency of endoscopy, and examination results between the two groups.Results Compared to GIB patients in initial stage of COVID-19 pandemic, prothrombin time (PT) (15.45 s vs 13.84 s, p = 0.003), activated partial prothrombin time (APTT) (33.13 s vs 27.28 s, p = 0.001), d-dimer (mg/L) (730.44 vs 507.22, p = 0.041), and prothrombin activity (PTA) (75.79% vs 76.61%, p = 0.001) were higher in GIB patients during COVID-19 pandemic. Furthermore, an increased need for ICU stays (%) (16.9% vs 3.8%, p = 0.020) and anticoagulant therapy (%) (38.2% vs 5.7%, p < 0.001), higher use of NSAIDs (%) (25.8% vs 3.8%, p = 0.001) and lower frequency of endoscopy (%) (41.6% vs 73.6%, p < 0.001) were seen during COVID-19 full-blown pandemic.Conclusion During COVID-19 full-blown pandemic, the number of patients with GIB increased significantly; these patients were more likely to require ICU admission. Although the endoscopic intervention rate was significantly reduced in COVID-19 patients, there were no significant differences in hospital stay, blood transfusion requirements, rebleeding rate, and mortality.